Penerapan Metode COCOSO dan TOPSIS untuk Pemilihan Lokasi Pembangunan Perumahan Kota Semarang - Edy Winarno; Taufiq Dwi Cahyono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
One of the important and complicated stages in the construction project development process is selecting the location to be built. Project success and customer satisfaction will be influenced by good location selection. It is very important to use a Decision Support System (DSS) to help make more organized and informed decisions in situations like this. This is an SPK proposal for a housing development location that combines the COCOSO (Combined Compromise Solution) and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) methods. The COCOSO method, which considers several conflicting criteria, was used to resolve doubts and site selection problems. Additionally, locations are ranked using TOPSIS based on how close they are to the ideal solution. Identify important factors that influence location selection including accessibility, land prices, infrastructure, and environmental factors. Next, assessment and ranking are carried out using COCOSO to provide the best compromise solution, and the results are evaluated using TOPSIS to determine the best location. A fictional case study is used to test system performance. Potential housing location data is used as an example. The simulation results show that the proposed SPK can provide complete and reliable location recommendations for housing developers. COCOSO and TOPSIS integrated in this SPK help decision makers choose locations by considering trade-offs between various criteria and choosing the location closest to the best solution. This SPK can help developers make strategic decisions about housing development locations.